The Influence of Social Class on Risk Behaviors Among College Students: The Mediating Role of Family Violence (European Journal of Behavioral Sciences, 2023)
In recent years, various kinds of risk behaviors among urban and rural adolescents have increasingly aroused public concern. To explore the influence mechanism of social class and family violence on risk behaviors and the mediating effect in this process, this study selected 216 students from universities in Beijing and Hebei for a questionnaire survey based on the principle of convenient sampling. The results of regression analyses and mediating effect analysis revealed that participants' subjective social class significantly predicted risk behaviors and family violence. Correlations between variables were verified, and family violence played a partial mediating role between social class and risk behaviors. Our findings echoed previous studies on the relationships between social class, risk behaviors, and family violence in pairs. Furthermore, this study innovatively proposed and constructed a mediating model of the relationship among the three variables through statistical analysis, which offered evidence support for subsequent researches in the field of educational psychology and also provided space for further studies related to family factors.